Added Value of Assessing Adnexal Masses with Advanced MRI Techniques. (27th August 2015) - Thomassin-Naggara, I.; Balvay, D.; Rockall, A.; Carette, M. F.; Ballester, M.; Darai, E.; Bazot, M.
Abstract : This review will present the added value of perfusion and diffusion MR sequences to characterize adnexal masses. These two functional MR techniques are readily available in routine clinical practice. We will describe the acquisition parameters and a method of analysis to optimize their added value compared with conventional images. We will then propose a model of interpretation that combines the anatomical and morphological information from conventional MRI sequences with the functional information provided by perfusion and diffusion weighted sequences.